Comportamento do sono e aleitamento materno em crianças de 12 a 18 meses de idade - Cerqueira, Ana Carolina Dantas Rocha (2016)
In childhood, adequate sleep is especially important for the influence it has on growth and development. Sleep disorders are increasingly prevalent and determine poor performance, affecting the health, sometimes very severe. This study aimed to analyze the sleep behavior and duration of breastfeeding in children aged between 12 and 18 months frequenters or not daycare. Cross-sectional study with 369 children 12-18 months old and his primary caregiver. Data collection occurred from November 2014 to May 2015, in public, private and health centers nurseries during the vaccination campaign, with the caregivers of children, through the application of two instruments: the Infant Sleep Questionnaire (ISQ) and a form containing information related to characterization of the participants, the child's sleep and breastfeeding. The variable study outcome was the sleep behavior measured by three criteria: the scores, the caregiver and the evaluator, contained in ISQ. Thus three logistic regression models were estimated using the Forward stepwise method and the final model only variables with p-value <0.05. It was found change in sleep behavior at the discretion of the scores, the criterion of the caregiver and the evaluator's criteria for 104 (28.2%), 102 (27.6%) and 85 (23.0%) children, respectively . It remained after adjustments, a statistically significant association with changes in sleep behavior: household sharing for more than three people; family income higher than four minimum wages; changes in the child's routine; not breastfeeding in the first hour of life; feed the child during the night for all nights of the week; not fall asleep pacifier; child to sleep after 20 hours, more than two hours during the day and six to eight hours to overnight. Breastfeeding time more than 12 months increased at twice the chances for changes in sleep behavior (OR = 2.00, CI 1.06 to 3.79); the inclusion of children in day care was not associated or duration of breastfeeding or the existence of changes in sleep behavior of children. Sleep behavior evaluation in children according to the ISQ is important screening method to be implemented in child care services. Keep the child in day care was not considered a determining factor for the failure of breastfeeding and was not associated with the behavior of sleep presented by them. Interventions by the caregivers of children who continue to be breastfed after the first year of life need to be planned so as to guide about the associated aspects, especially the maintenance of the practice of co-sleeping, the habit of offering the breast to the child falls asleep and offering the breast the child during the night, to minimize sleep problems in this population and help prevent the establishment of recurring problems, potentially causing sleep disorders.